Ophthalmological changes in celiac disease: A review of the literature - Ana Beatriz Piromali dos Santos; Júlia Mendes Lima; Andressa Paulon Silva; Gabriella Fouraux Gouvêa; Thais Piedade de Andrade; Eric Pinheiro de Andrade (The Pan-American Journal of Ophthalmology, 2025)
Celiac disease is a chronic autoimmune enteropathy triggered by gluten ingestion in genetically predisposed individuals, which affects approximately 1% of the world population. The main genetic factors associated with the development of celiac disease are human leukocyte antigens, mainly types DQ2 and DQ8, for which most patients with this condition are positive. It is known that the inflammatory process present in celiac disease is mediated especially by CD4 T-cells, antibodies against wheat gliadin, and the enzyme transglutaminase 2. The classic form of celiac disease is characterized by gastrointestinal symptoms, although extraintestinal manifestations can be found in more than 50% of cases, including visual changes. The pathophysiological mechanisms of ophthalmological manifestations associated with celiac disease include malabsorption and autoimmune dysfunctions, capable of leading to involvement of the anterior and posterior segments of the eye. This review aims to gather the main ophthalmological manifestations associated with celiac disease, as well as to explain its pathophysiological mechanisms.